2021
DOI: 10.1080/02670836.2021.1911444
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of solidification modes of high Manganese steels

Abstract: The solidification modes of high manganese steels were measured by experiments and comparatively calculated by different predicted methods. The DSC experiments indicate the same phase transformation sequence as the isothermal solidification experiments. It is demonstrated that the solidification modes of the Fe–0.028C–21.1Mn–5.72Al, Fe–0.28C–21.0Mn–5.80Al and Fe–0.64C–21.0Mn–5.80Al alloys are F mode, FA1 mode and FA2 mode. The change of heating/cooling rate influences the position and shape of the peaks in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…How to control AlN precipitation has not yet reached to a consistent conclusion. Liu et al [12][13][14][15] have carried out a series of basic research on the microstructure and high temperature mechanical properties of TWIP steel, and counted the evolution of stored dislocation density and deformation twins, as well as their respective contributions to the strengthening and the work hardening. Xin et al 16) found that the dominant stable inclusion changed from MnO to Al 2 O 3 /MnS, MnS, and AlN with the increase of Al content from 0.002 to 2.1 mass% in the Fe-16Mn-Al-0.6C alloys.…”
Section: Introductionmentioning
confidence: 99%
“…How to control AlN precipitation has not yet reached to a consistent conclusion. Liu et al [12][13][14][15] have carried out a series of basic research on the microstructure and high temperature mechanical properties of TWIP steel, and counted the evolution of stored dislocation density and deformation twins, as well as their respective contributions to the strengthening and the work hardening. Xin et al 16) found that the dominant stable inclusion changed from MnO to Al 2 O 3 /MnS, MnS, and AlN with the increase of Al content from 0.002 to 2.1 mass% in the Fe-16Mn-Al-0.6C alloys.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies were limited in their ability to directly observe structural transformations during solidification and phase interface growth kinetics. Shen et al [11] investigated the high-temperature solidification process of Fe-Mn-C-Al system high-manganese steel through isothermal quenching experiments and directly observed the solidification structure at different temperatures through metallographic examination. Li et al [12] revealed the effect of Ce on the solidification structure through directional solidification experiments from both micro-and macro-perspectives.…”
Section: Introductionmentioning
confidence: 99%